"Alors, on va faire une activité": An SFL perspective on student engagement in contextualized world language instruction. (June 2021) - Troyan, Francis John
Abstract: Contextualized language instruction has been critiqued for lacking a linguistic knowledge base and guidelines for pedagogy. In response, systemic functional linguistics (SFL) and the associated genre theory have been advanced as both a knowledge base for world language teaching and a means for contextualized language instruction; however, little research has examined world language teachers' enactment of contextualized instruction informed by this theory. In response, this study used the appraisal system to describe how Brahim, a French immersion teacher, engaged his students in contextualized instruction. Using Christie's (2002) framework for discourse analysis, I describe how Brahim interactively contextualized language learning with his students across three curriculum genres focused on teaching students to write the report on plans genre. The findings demonstrate 1) the potential of SFL-informed genre pedagogy for enacting contextualized world language instruction and 2) the use of the appraisal system for understanding how a teacher's positive affect, judgement, and other engagement strategies of pedagogical discourse invite students into contextualized instruction.